Clergy-Laity Conflicts Over Nigerian Baptist Policies in Ogbomoso Conference, 1993 – 2008 (2014)
Baptist policies regarding clergy-laity practices and benefits have been properly documented and approved by the Nigerian Baptist Convention. Despite the approval, some pastors and members had flouted these policies resulting in conflicts in some places, especially in Ogbomoso Baptist Conference between 1993 and 2008. Existing studies have concentrated on misuse of power and inter-personal relationship in multi-staff ministry with little attention paid to conflicts arising from Baptist policies. This study, therefore, examined the policies, causes of the conflicts resulting from their implementation and the effects on the church with a view to providing suggestions toward policy-oriented conflicts reduction. The study adopted Buse's Policy Implementation theory. A total of 345 copies of a questionnaire were administered to 58 pastors and 287 laity from purposively selected churches in Ogbomoso metropolis: Ijeru Baptist Church, Ebenezer Baptist Church, Ori-Oke Baptist Church and Iranlowo-Oluwa Baptist Church. In-depth interviews were conducted with purposively selected 20 clergymen and 20 laity. Church records were consulted. Data were subjected to historical analysis and percentages. The Nigerian Baptist denomination has four policies relating to church administration: non-accordance of church-membership to known members of secret societies; non-allowance of pastors to engage in herbal medicine; monogamy as a requirement for holding church offices and pegging of pastors‘ retirement age to 65 years. Between 1993 and 2002, the Ebenezer Baptist Church pastor's insistence that members should publicly renounce secret societies as attested to by 88.2% of clergy and 91.8% of laity caused conflicts, resulting in the assault on the pastor. Also, Christian burial rites were denied members who did not renounce the societies. This resulted in withdrawal of membership by a number of individuals. The non-allowance of the pastor of Ijeru Baptist Church to engage in herbal medicine in 2001 attested by 94.1% of clergy and 50.6% of laity led to his sack. The ensuing conflict resulted in the disruption of church services, to which Oodua Peoples Congress, a Yoruba socio-cultural militant group, was invited. Also, splits occurred which reduced attendance, and led to the pastor's eventual vacation of the church. Refusal to appoint polygynists as church officers at Iranlowo-Oluwa Baptist Church precipitated conflicts between 2003 and 2008 as claimed by all pastors and 97.0% of laity. The consequence was the disruption of church services normalized by police intervention. Also, splitter groups emerged: one moved out of the church to form a new church headed by the incumbent pastor; the other stayed back, headed by the lay leader. The unwillingness of pastors to go on retirement at age 65 as confirmed by 58.8% of pastors and 94.2% of laity ignited conflicts in Ori-Oke Baptist Church and Ebenezer Baptist Church in 2006 and 2007 respectively. The conflicts resulted in secession, derobing of one pastor and unceremonious retirement of the two pastors. The violation of Baptist polices on church administration led to pastor-laity conflicts in Ogbomoso Baptist Conference, 1993-2008, resulting in assault, loss of corporate face, membership and jobs. There is a need for great enlightenment on Baptist policies to avoid intra-denominational conflicts